Identification And Enumeration Of Asbestos Fibers In The Mining Environment: Mission And Modification To The Federal Asbestos Standard - Arthur M. Langer (Society for Mining, Metallurgy & Exploration, 2008)
Since the promulgation of the first Federal Asbestos Standard by the Occupational Safety and Health Administration in 1972, other federal agencies have modified the standard to better carry on their own unique missions. The instruments used to identify and measure asbestos, the sampling protocol, and the criteria used to define asbestos, have been modified to some degree. The Mine Safety and Health Administration regulates and controls asbestos dust in the mining and mineral commodity industries. However, crushed stone and processed ores contain mineral fragments that are frequently difficult to distinguish from asbestos. Mineral nomenclature, instruments for particle analysis, and sampling strategy must be accommodated to some degree to make asbestos control workable and meaningful. Precedent in other agencies has made consideration of these changes possible. Newly identified amphibole asbestos minerals have further complicated the agency?s regulatory charge. Changes in its Asbestos Standard are now being considered. Crushed taconite ore in the Eastern Mesabi highlights many of these issues. ©2008 Published by Elsevier Inc. Keywords: Amosite; Grunerite asbestos; Crocidolite; Riebeckite asbestos; Tremolite asbestos; Actinolite asbestos; Winchite asbestos; Richterite asbestos; Arfvedsonite asbestos; Fluor-edenite asbestos; Asbestos defects; Cleavage fragment; Mineral habit; Mesabi amphiboles